The Accidental Capture of a Newborn Shortfin Mako Shark Isurus oxyrinchus (Rafinesque, 1810) in the Northwestern Mediterranean Sea off the Coast of Marseille, France - Leguay, Emmanuel; Clua, Eric E. G. (Oceans (Basel, Switzerland), 2025)
A small-sized shark was accidentally caught in the coastal waters of southeastern France and abandoned in the port of L’Estaque (Marseille) in May 2024. An autopsy revealed that it was a young female shortfin mako, Isurus oxyrinchus (Rafinesque, 1810). Numerous superficial wounds on the head, back, and flanks, in the form of parallel striations resulting from heavy friction, indicate meshing in a gillnet that provoked the animal’s death by asphyxiation. Its very small size (64.77 cm TL) suggests that this is a newborn individual, leading to the hypothesis that the waters off Marseille could be a nursery area for this species. This observation alone is not enough to prove this point, but it does suggest the need for closer monitoring to validate it. Should the area be proven to play this key role for this critically endangered species, measures to limit fishing pressure would be essential, particularly during the parturition period between February and May.